1972
DOI: 10.1083/jcb.52.3.733
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Changes of Proteins of Endoplasmic Reticulum

Abstract: The proteins of the smooth and rough endoplasmic reticulum from fetal, immature, and adult male rats were compared after incorporation of two radioactively labeled precursors, "C-labeled amino acids and S-aminolevulinic acid 3 H by means of gel electrophoresis. The labeling patterns indicated that protein components present in two major electrophoretic bands underwent significant synthesis in fetal tissue while three actively incorporating protein bands were noted in adult tissue . Although the uptake of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The results point to the conclusion that during differentiation of the ER membranes, at least one protein, cyt P450, is present in an inactive form, without its heme moiety, and that differentiation consists, in part, of the attachment of heme to the apo-protein concomitant with an increase in the proportion of this protein in the membranes. A similar conclusion has been reached for this cytochrome based on preliminary evidence (53).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results point to the conclusion that during differentiation of the ER membranes, at least one protein, cyt P450, is present in an inactive form, without its heme moiety, and that differentiation consists, in part, of the attachment of heme to the apo-protein concomitant with an increase in the proportion of this protein in the membranes. A similar conclusion has been reached for this cytochrome based on preliminary evidence (53).…”
Section: Discussionsupporting
confidence: 84%
“…This result, which confirms an earlier one (45), is not too surprising since the hemes of cyt P4so and cyt bs are noncovalently bound to the proteins, can be removed by 7 M urea (52), and have been shown recently to be also removed by SDS (45). A contrary finding has been found, that is, a retention on SDS gels of label from ,'-ALA injection (53); but this may possibly be due to a dissociation and reassociation of heme to proteins on the gel under the conditions of the experiment, as will be explained below. Schatz et al (54) have found that by treating mitochondria1 fractions with alkaline h'ig.…”
Section: Identification Of Major Band As Apo-cyt Pa0supporting
confidence: 88%
See 1 more Smart Citation
“…1 Added BF was dissolved in 10 µl ethanol. 2 These assays were performed on fresh tissue preparations. 3 These assays employed tissues which had been previously frozen ( -80 °C; 1 weck).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it is still unclear how heme generated in the mitochondria is delivered and inserted into CYP proteins. Early studies suggested that CYP heme acquisition might occur in concert with their protein expression ( 13 ), but other studies indicated that CYP proteins may build up in their heme-free forms during their maturation ( 14 , 15 ), particularly in tissues other than the liver including the brain, lung, and kidney ( 16 , 17 ). Given the propensity of CYP’s to attach to the ER, it has also been suggested that heme delivery to such proteins might occur through mitochondrial-ER membrane contact ( 18 ).…”
mentioning
confidence: 99%